Pengaruh Motivasi Belajar, Kemandirian Belajar, Executive Function, dan Rasa Percaya Diri Terhadap Kemampuan Literasi Matematis Siswa (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the influence of learning motivation, learning independence, executive function, and confidence on students' mathematical literacy skills. This research is a quantitative research. The research sample consisted of a number of high school students who were selected through random sampling techniques. Data were collected through questionnaires and mathematical literacy tests, then analyzed for path analysis to determine the contribution of each independent variable to the dependent variable. The results showed that there was a significant influence between learning motivation, learning independence, executive function, and confidence on students' mathematical literacy skills, both partially and simultaneously. There is an influence between learning motivation, learning independence, and self-confidence directly on executive function. Literacy ability is directly influenced by executive function and learning motivation significantly. Meanwhile, learning independence and self-confidence do not have a significant direct effect on mathematical literacy skills. However, learning independence and self-confidence affect mathematical literacy skills indirectly through executive functions. These findings show that strengthening psychological and cognitive factors is indispensable in improving students' mathematical literacy.